2004
DOI: 10.1086/422454
|View full text |Cite
|
Sign up to set email alerts
|

Fever after Immunization: Current Concepts and Improved Future Scientific Understanding

Abstract: Fever is a common clinical complaint in adults and children with a variety of infectious illnesses, as well as a frequently reported adverse event following immunization. Although the level of measured temperature indicative of a "fever" was first defined in 1868, it remains unclear what role fever has as a physiologic reaction to invading substances, how best to measure body temperature and compare measurements from different body sites, and, consequently, how to interpret fever data derived from vaccine safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
1
8

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 52 publications
0
48
1
8
Order By: Relevance
“…[8][9][10] Fever retards the growth and reproduction of bacteria and viruses, enhances neutrophil production and T-lymphocyte proliferation, and aids in the body's acute-phase reaction. [11][12][13][14] The degree of fever does not always correlate with the severity of illness.…”
Section: Physiology Of Fevermentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] Fever retards the growth and reproduction of bacteria and viruses, enhances neutrophil production and T-lymphocyte proliferation, and aids in the body's acute-phase reaction. [11][12][13][14] The degree of fever does not always correlate with the severity of illness.…”
Section: Physiology Of Fevermentioning
confidence: 99%
“…7,9,[21][22][23] Fever is a common and normal physiologic response that results in an increase in the hypothalamic "set point" in response to endogenous and exogenous pyrogens. 9,23 In contrast, hyperthermia is a rare and pathophysiologic response with failure of normal homeostasis (no change in the hypothalamic set point) that results in heat production that exceeds the capability to dissipate heat. 9,23 Characteristics of hyperthermia include hot, dry skin and central nervous system dysfunction that results in delirium, convulsions, or coma.…”
Section: Physiology Of Fevermentioning
confidence: 99%
“…7 Parents should realise that fever is not an illness, but is, in fact, a physiological mechanism that has beneficial effects in fighting infection. 8,9 A study by Crocetti et al indicated that parents still have a limited understanding of fever. Also, they found little change in the knowledge of American mothers, beliefs and practices over a 20-year interval.…”
Section: Introductionmentioning
confidence: 99%
“…Parents should know that fever is not an illness, but is, in fact, a physiological mechanism that has beneficial effects in fighting infection. 8,9 The practice of alternating two types of antipyretics has become widespread at home and paediatric wards, but is this method supported by evidence and does it results in complications? 36 There is still a significant contrast between scientific evidence on the one hand and current concepts and practices on the other.…”
mentioning
confidence: 99%
“…5 Before 2009, infants commonly received prophylactic acetaminophen treatment to prevent immunization discomfort and fever, although there is a low level of evidence for effectiveness. [6][7][8] In 2009, Prymula et al 9 published data from a randomized controlled trial (RCT) that showed reduced immunogenicity when infants (3-5 months of age) received 3 doses of acetaminophen in the first 24 hours after primary vaccines. This led some authors to reconsider the practice, 10 whereas others advocated maintaining the current practice.…”
mentioning
confidence: 99%